Collaboration between Parents and Islamic Education Teachers on Elementary Students’ Religious Achievement - Andini, Riddo; Syahminal, Syahminal; Nusir, Lidia; Desriri, Intan; Syafitri, Yunita; Jaslin, Raffi (Ahlussunnah: Journal of Islamic Education, 2026)
Collaboration between parents and teachers plays a strategic role in strengthening religious education among elementary school students, particularly in shaping worship habits, moral conduct, and learning motivation grounded in religious values. This issue has become increasingly important due to the challenges posed by social and technological developments that influence children's religious behavior. This study aims to analyze the forms of collaboration between parents and Islamic Education teachers and to examine its impact on students’ religious achievement at the elementary school level. This research employs a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation. The data were analyzed systematically through data reduction, data display, and conclusion drawing. The findings reveal that collaboration is manifested through intensive communication between school and family, parental support in fostering worship practices at home, and the synergy in implementing school religious programs, such as extracurricular activities and daily religious routines. This collaboration contributes positively to improving students’ abilities in worship practices, moral behavior, and active participation in religious activities. The study concludes that sustained partnerships between parents and teachers are a crucial factor in developing students’ religious achievement. The stronger the collaboration established, the more optimal the students’ religious development in terms of knowledge, attitudes, and worship practices.